The stability of magnetized non-neutral plasma flow with a broad velocity distribution - Tarasov, M.I.; Tarasov, I.K.; Sitnikov, D.A.; Pashnev, V.K. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The stability of the magnetized non-neutral plasma cylindrical flow was studied experimentally. The flow is injected into the drift tube and spreads along its axis. The radial motion of the charged particles is limited by longitudinal magnetic field. During the experimental study the influence of such factors as the magnetic field strength and the average flow velocity on stability of the flow fluctuations was investigated.